Modelling of food security in Malaysia - Bala, Bilash Kanti; Alias, Emmy Farha; Mohamed Arshad, Fatimah; Mohd Noh, Kusairi; Abdul Hadi, Ahmad Hanis Izani (Elsevier, 2014)
Food security policy in Malaysia is largely about ensuring the availability, accessibility and utilization of rice to the society. To this end, three policy objectives were set since 1970s, namely: to ensure high price to paddy farmers to produce rice, to achieve a certain level of self-sufficiency in rice and to ensure a stable and high quality of rice to the consumers. To ensure these three-pronged objectives are met, the government has embarked on a protectionist regime to ensure the sector is insulated from the market vagaries particularly supply and price shocks. The instruments implemented include; price control (farm and retail), subsidies and income transfer, licensing and import monopoly. The interventions are deep and extensive in that the industry is highly distorted and begun to show some rigidities and inefficiencies. After the successful Green Revolution in the 1970s, paddy productivity has been slowing down in terms of annual rate of change. By 1990s, the chemical intensive culture introduced by the Green Revolution had started taking a toll. Evidences of reduction of soil fertility and water quality were rampant. While the other parts of the world are experiencing technological advances in paddy farming, Malaysia’s farmers remain conventional in their practices due to poor extension services. Hence, this study attempts to rectify these problematic and complex situation by proposing the need for more R&D (Research and Development) for higher yielding varieties, application of bio-fertilisers and new approach of extension (through farmer field schools). Towards these ends, the study has adopted the system dynamics methodology to capture the circular causality between variables in the paddy and rice system as well as delays and non-linearities. The findings suggest that gradual transition to bio-fertilizers, funding for R&D for development of high yielding hybrid rice and increasing the cropping intensity hold big promise towards productivity enhancement. The promotion of training and extension services using participatory approach of learning by doing or the farmer field schools is desirable to reduce the productivity gaps.